Analisis Dampak Negatif Dan Positif Model Pembelajaran Flipped Classroom di Universitas Negeri Makassar - Akmal Hidayat; Putri Mayang Sari; Muhammad Ubaidillah; Muh Alif Dzulfaqaar M; Muhammad Sadidan; Syafiqah Al Faiqah (Jurnal Pendidikan Terapan, 2023)
The purpose of this study is to determine the negative and positive impact of flipped classroom, Department of Informatics and Computer Engineering, Makassar State University, this type of research is as a whole, namely research and development. In this article, the research design used is evaluative research. The subject of this study was a student majoring in informatics and computer engineering, Makassar State University. Data collection techniques by distributing questionnaires to students majoring in informatics and computer engineering, the results of filling out online questionnaires filled out by students. Meanwhile, at the data analysis stage, descriptive analysis is carried out. That the activeness of students of the Department of Informatics & Computer Engineering Makassar State University in the flipped classroom learning model can be said to be good